Intervention Reduce anxiety in CHF patients (Congestive Heart Failure): Systematic Literature Review - Aurellia Firstania; Azizah Khoiriyati (Universitas Aisyah Pringsewu, 2023)
Background: Psychological problems in CHF patients result from a combination of behavioural influences and interaction with physiologic responses that, if not managed appropriately clinical symptoms may worsen and the risk of hospitalization may increase. People with congestive heart failure (CHF) often experience physical pain and anxiety. Anxiety is associated with an increased risk of death in people with CHF. Objective: This study aims to determine interventions that can be used to reduce patient anxiety. This review was carried out because previously no one had reviewed interventions to reduce stress in CHF patients. Method: Use systematic literature retrieval methods by tracking library resources through journal databases the Pubmed, ProQuest, Science Direct, Scopus and Google Scholar in 2013-2022. Inclusion criteria in this review are: English journals, journals and journals researching CHF patients who experience anxiety; the research design is a quasi-experimental, randomized controlled trial, actual experimental and intervention study. Result: Based on the study, obtained seven journals for review and several interventions could reduce anxiety in patients with CHF, namely back massage intervention, schema therapy, tai chi cardiac rehabilitation program, breathing training, walking with controlled breathing, back massage therapy, and cognitive behavioural therapy. Conclusion: This review concludes that all interventions are significant for anxiety in CHF Patients. Abstrak: Latar Belakang: Masalah psikologis pada pasien CHF merupakan akibat kombinasi dari pengaruh perilaku dan interaksi dengan respon fisiologis, yang jika tidak ditangani dengan baik akan berkontribusi pada perburukan gejala klinis dan memiliki risiko rawat inap yang lebih tinggi. Pasien yang menderita gagal jantung kongestif (CHF) sering merasakan penderitaan fisik dan kecemasan. Kecemasan dikaitkan dengan peningkatan risiko kematian pada pasien dengan CHF. Tujuan: Penelitian ini bertujuan untuk mengetahui intervensi yang dapat digunakan untuk mengurangi kecemasan pada pasien. Review ini dilakukan karena sebelumnya belum ada yang melakukan review tentang intervensi untuk menurunkan kecemasan pada pasien CHF. Metode: Pencarian literatur yang sistematis digunakan sebagai metode dengan penelusuran sumber pustaka melalui databased jurnal Pubmed, ProQuest, Science Direct, Scopus dan Google Scholar tahun 2013-2022. Kriteria inklusi dalam review ini adalah jurnal berbahasa Inggris, jurnal dan jurnal yang meneliti pasien CHF yang mengalami kecemasan, desain penelitian yaitu quasi eksperimental, randomized controlled trial, true experimental dan intervention study. Hasil: Berdasarkan telaah didapatkan 7 jurnal untuk di review dan beberapa intervensi yang dapat mengurangi kecemasan pada pasien dengan CHF yaitu back massage intervention, schema therapy, tai chi cardiac rehabilitation program, breathing training, walking with controlled breathing, back massage therapy, cognitive behavioral therapy. Kesimpulan: Kesimpulan dari tinjauan ini adalah bahwa semua intervensi untuk kecemasan pada pasien CHF bermakna.